從中國生命倫理學到複製人類的道德問題——一個方法學上的省思: From Chinese Bioethics to Human Cloning - A Methodological Reflection - CHAN, Jonathan (International Journal of Chinese & Comparative Philosophy of Medicine, 1998)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文的主要目的是要說明怎樣建構一具普遍意義的中國生命倫理學。在本文的第一部分裏，筆者提出了一個“三層架構”的方法學框架來說明建構具普遍意義的中國生命倫理學的可能性。本文的第二部分則主要是通過考察複製人類的道德問題為上述的建構工作提供一個實例。在這個部分裏面，筆者提出了一個儒家傳統的中介原則的理論框架，並通過此一理論框架來考察複製人類的道德問題。根據有關的中介原則，複製人類是否道德上可接受主要視乎複製人類的活動是否會對別人構成傷害。筆者分別考察反對者經常採用的（亦是最主要的）兩個“傷害論証”，並指出它們皆含有不合理的前提。 This paper aims to tell a story about Chinese bioethics that appears to be attractive. The crux of it is to show how to work out a Chinese bioethics which is able to retain enough essential elements of Chinese philosophy and at the same time to provide guidance and advice rationally acceptable to the citizens of a constitutional democratic society as to bioethical issues. The crucial part of the story is to exhibit a methodological framework for such Chinese bioethics. I shall take up this job in the first part of this paper. In the second part of this paper, I shall make use of this methodological framework to analyze the ethics of human cloning. This paper begins by specifying three major tasks of Chinese bioethics: (i) delineate the scope of fundamental questions of Chinese bioethics; (ii) carry out what I shall call an ’internal survey’ of the traditions of Chinese philosophy in relation to bioethical issues; (iii) provide ethical rules and guidance for the public sphere as to bioethical issues. With respect to the first task, this paper proposes to distinguish three areas of questions. The first area consists of those bioethical questions that are of current interest and concern to bioethicists in general. The second area consists of those bioethical questions that are peculiar to the traditions of Chinese philosophy. For instance, Confucianism takes familial relationship and virtues as of utmost importance. Then, how to formulate a health care policy that can enhance the familial relationship among family members and virtues of individuals would be a question of great concern to the Confucian. The third area consists of questions that are particularly related to the methodology of Chinese bioethics. For instance, how to lay out a sound methodology for Chinese bioethics is a question that belongs to this area. As to the second task, the aim is to reconstruct the fundamental bioethical principles of the philosophical traditions of Chinese philosophy and apply these principles to the bioethical issues. In accomplishing this aim, we need to study the relevant documentarymaterials as well as the comprehensive doctrines of the philosophical traditions of Chinese philosophy and to deduce or formulate the relevant principles on the basis of this study. Now let us turn to the third important task of Chinese bioethics, which is the most challenging one among the three. Before probing into the crux of this task, some preliminaries are in order. First, the idea of public sphere is understood here as a conception of public sphere that belongs to a conception of a constitutional democratic society. It is defined as a sphere generated by the communicative actions of all equal and free citizens of a constitutional democratic society, the purpose of which is to provide point of views, reasons, rules or procedures for resolving conflicts among these citizens. Second, as a basic feature of a constitutional democratic society, citizens who are involved in the public sphere are expected to belong to different religious, philosophical or moral traditions and therefore hold very different or even conflicting comprehensive doctrines. A comprehensive doctrine, to follow Rawls’ use, ’includes conceptions of what is of value in human life, and ideals of personal character, as well as ideals of friendship and of familial and associational relationships, and much else that is to inform our conduct, and in the limit to our life as a whole.’ And it is unlikely that we can provide rational arguments to settle the question of truth in respect of these comprehensive doctrines or to show that one of the existing comprehensive doctrines is the best among others. Given these two preliminaries, we can see why the third task of Chinese bioethics is so challenging: In the first place, its major aim, as specified above, is to provide ethical rules and guidance for the public sphere as to bioethical issues. And the public sphere isconstituted by the communicative actions of all equal and free citizens. Then, if this task is to succeed, the ethical rules and guidance provided must be rationally acceptable to these citizens. In the second place. as we have pointed out, in a constitutional democratic society, citizens may belong to different religious, philosophical or moral traditions whose comprehensive doctrines are so different or even conflicting. In other words, in such a society, a citizen can be a Confucian, Protestant, Muslim, Buddhist, Taoist, Catholic or a member of any other traditions. In the third place, since Chinese bioethics is founded upon Chinese philosophy, the ethical rules and guidance in question must be heavily shaped by the comprehensive doctrines of the traditions of Chinese philosophy. Then how is it possible for Chinese bioethics to succeed in providing ethical rules and guidance that are also rationally acceptable to those citizens belonging to the traditions other than those of Chinese philosophy? Here is the dilemma: On the onehand, if the ethical rules and guidance in question are so heavily shaped by the comprehensive doctrines of the traditions of Chinese philosophy, then there is no reason to expect citizens who belong to other traditions to accept them. On the other hand, if the ethical rules and guidance in question have nothing, or too little, to do with the traditions of Chinese philosophy, then Chinese bioethics will lose its distinctiveness. This paper proposes a ’three-levels’ methodological framework to solve the above dilemma. This methodological framework includes three different parts: (i) the fundamental moral principles of a tradition; (ii) intermediate principles; and (iii) overlapping consensus about bioethical issues. The basic idea of this framework rests on the fact that although different traditions have different or even conflicting comprehensive doctrines, they may have overlapping consensus about bioethical issues. This consensus is a set of bioethical judgements commonly affirmed by the comprehensive doctrines of different traditions. The crucial step of the framework is to develop some intermediate principles of a tradition on the basis of this consensus. The intermediate principles developed have to satisfy two requirements. First, they imply only the bioethical judgements of the overlapping consensus. Second, they must have logical connection with the fundamental moral principles of the tradition. To apply this methodological framework to Chinese bioethics, we first need to identify the fundamental moral principles of the traditions of Chinese philosophy and then to derive the intermediate principles from these fundamental moral principle. The second part of this paper attempts to apply the above methodological framework to develop a set of intermediate principle that are related to the tradition of Confucianism and use them to discuss the ethics of human cloning. They are listed as follows: (i) ’Do no harm’ principle; (ii) ’Freedom to reproduce’ principle; (iii) ’Causing to exist can benefit’ principle; (iv) ’Freedom to know’ principle; (v) ’Knowledge as a kind of human good’ principle; (vi) ’Will-based’ non-identity principle. It is the present author’s view that, as long as cloning human beings does not harm any human person, research directly or indirectly related to human cloning should not be entirely prohibited. It will be argued in this part that this view is supported by the above intermediate principles. Briefly, according to the ’Do no harm’ principle, if cloning human beings will cause harm to some human person, then researchers should not be allowed to do so. Nevertheless, if cloning human beings does not harm any human person, then both the ’Freedom to reproduce’ principle and the ’Knowledge as a kind of human good’ principle support researchers’ freedom to clone. Thus, the kernel of the discussion is whether cloning human beings will cause harm to some human persons. Some people do think that cloninghuman beings is morally objectionable on the ground that it will cause harm to others. This paper will focus on those harm-based objections. Two major harm-based objections will be discussed and it will be argued that these two harm-based objections are flawed. DOWNLOAD HISTORY | This article has been downloaded 21 times in Digital Commons before migrating into this platform.